Rational Emotive Behavior Group Counseling to Reduce Toxic Masculinity in the Patriarchal Culture of High School Students - Habsy, Bakhrudin All; Amania, Rukhil; Omoyemiju, Michael Adeniyi (Jurnal Kajian Bimbingan dan Konseling, 2025)
Toxic masculinity is a social construct in patriarchal societies, characterizing male attitudes that dominate and accentuate gender inequality with women in lower positions, influencing detrimental behavioral patterns. This research aims to examine the effectiveness of Rational Emotive Behavior Group Counseling in reducing toxic masculinity behaviors among high school students within the context of patriarchal culture. The study employed an experimental design with a pretest and posttest control group arrangement. From the Toxic masculinity inventory measurements, twelve students with high levels of toxic masculinity characteristics were identified. Subject selection was randomized, with six students in each experimental and control group. Data collected were analyzed using a paired sample T-test, revealing a significance value of 0.000 (<0.05). Therefore, the null hypothesis (Ho) was rejected, indicating that Rational Emotive Behavior Group Counseling is effective in reducing toxic masculinity behaviors among high school students influenced by patriarchal culture. This research contributes to understanding the effectiveness of group counseling interventions with the Rational Emotive Behavior Group Counseling approach in addressing the impact of toxic masculinity. The implications have the potential to transform student behavior towards gender balance and equality within the patriarchal culture of high school education environments.